PEMANFAATAN ARTIFICIAL INTELEGENCE DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA SEKOLAH DASAR - Listi, Alifia; Safiqa, Nurul; Wahyu Pamungkas, Danang; Adrias, Adrias; Chandra, Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy is a crucial basic skill for elementary school students because it plays a role in understanding information and supporting the success of the learning process. However, elementary school students' reading literacy skills still show a concerning condition, particularly in aspects of letter recognition, text comprehension, and the ability to analyze and evaluate information. This study aims to analyze the use of artificial intelligence (AI) in improving elementary school students' reading literacy and identify the most effective AI media. This study used a literature study method by reviewing various sources such as scientific journals and relevant articles. Data were analyzed through a process of collecting, comparing, and combining previous research results to determine the effectiveness of using AI in improving students' reading skills. The study results show that the application of artificial intelligence in the reading learning process provides significant positive results for improving students' reading skills, both in terms of fluency, comprehension, and motivation to learn. Of the several AI media analyzed, Google Read Along showed the most satisfactory results, as evidenced by the significant increase in scores and its ability to provide customized learning and real-time feedback. Therefore, it can be concluded that the use of AI, especially Google Read Along, is an effective strategy in improving students' reading literacy at the elementary level and is very suitable for learning needs in the digital age.